2017
DOI: 10.1186/s11556-017-0171-9
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of physical activity among elderly residents and professionals in assisted living facilities

Abstract: BackgroundPhysical activity is often described as being important for people of all ages, but what different people mean when they talk about physical activity is unclear.MethodA phenomenographic method was used to analyze how 13 older people and 17 professionals answer the question, “If I say physical activity, what does the concept mean to you?” as part of semi-structured interviews conducted in four assisted living facilities in two different municipalities.ResultsWe identified a number of different percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 24 publications
0
1
0
2
Order By: Relevance
“…Ekerdt () suggested that older people were compelled to keep busy and occupied as a way of justifying their leisure. Mahrs Träff, Cedersund, and Nord () found that older resident in assisted living facilities considered physical activity as a way to create meaning and to maintain or enhance bodily function. Similarly, despite a gradual decline in intensity, older people living in the community tended to continue engaging in meaningful physical activities such as walking and gardening if they had support to adjust to limitations associated with ageing (Janssen & Stube, ).…”
Section: Discussionmentioning
confidence: 99%
“…Ekerdt () suggested that older people were compelled to keep busy and occupied as a way of justifying their leisure. Mahrs Träff, Cedersund, and Nord () found that older resident in assisted living facilities considered physical activity as a way to create meaning and to maintain or enhance bodily function. Similarly, despite a gradual decline in intensity, older people living in the community tended to continue engaging in meaningful physical activities such as walking and gardening if they had support to adjust to limitations associated with ageing (Janssen & Stube, ).…”
Section: Discussionmentioning
confidence: 99%
“…Äldre personer har beskrivit fysisk aktivitet som gymnastik och promenader (Mahrs Träff, Cedersund & Nord, 2017). Personal har beskrivit att fysisk aktivitet för personer som bor på särskilt boende är att genomföra vardagsaktiviteter t.ex.…”
Section: Terminologiunclassified
“…Personal har beskrivit att fysisk aktivitet för personer som bor på särskilt boende är att genomföra vardagsaktiviteter t.ex. att äta och att klä på sig själv (Mahrs Träff et al, 2017).…”
Section: Terminologiunclassified